The political significance of popular illegalities in post-apartheid South Africa - McMichael, Christopher Bryden (Rhodes University, Faculty of Humanities, Department of Political and International Studies, 2008)
This thesis discusses the significance of popular illegalities in contemporary South African service delivery. Illegal access to and non-payment of services have been indentified by the government as a major criminal problem which undermines effective service delivery. By contrast, this thesis argues that popular illegalities are positive phenomenon which provides otherwise unobtainable benefits for the poor and also exposes the ability of communities to self-manage their own service provision. The thesis begins by surveying a variety of literature on this issue using both contemporary and historical literature. I then discuss the scope of popular illegalities in South Africa and the methods government has used to curtail them, with a particular emphasis on how this has been influenced by the adoption of neo-liberal cost recovery initiatives. Using case studies of three communities where illegal access is prevalent, I discuss both the motivations behind and significance of illegal water and electricity connections. In conclusion, I argue that popular illegalities are a significant phenomenon in so far as they suggest new methods of delivering services. The prevalence of these illegalities is also important as it highlights many of the failings of official delivery. The thesis concludes on a hopeful note in arguing that illegalities may be inherently progressive in both benefiting the marginal and leading to the creation of radically autonomous spaces which can be viewed as laboratories of radical social change.
Keywords: Illegality -- South Africa -- Case studies; Legal services -- South Africa; Post-apartheid era -- South Africa; South Africa -- Politics and government -- 1994-